(untitled) (American Journal of Language, Literacy and Learning in STEM Education (2993-2769), 2025)
This study introduces the Educator-AI Multimedia and Real-Life Awareness Method (EAMM-R), an innovative approach designed to enhance personalized learning, emotional engagement, and real-life awareness among students. The method integrates artificial intelligence, multimedia tools, and reflective learning strategies to address individual differences in learning pace, emotional states, and comprehension levels. The results demonstrate that EAMM-R significantly improves students’ motivation, self-awareness, and learning performance through adaptive feedback and emotional support mechanisms.